Extraspinal incidental findings of spinal MRI - Joori, Salam M.; Albeer, Mays R.; Al-Baldawi, Duraid S. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Magnetic resonance imaging (MRI) is the modality of choice for investigation of disorders of the spine. The use of spinal MRI imaging has increased over the last few years, with improvement in hardware such as magnets, coils as well as imaging techniques. Which should lead to accurate reporting of these examinations includes identifying the incidental abnormalities even if they are not related to the spine. Objective: The objective is to evaluate the incidence, types and associated variables of Patients and methods: A retrospective study of 507 patients was reviewed for MRI spine at Baghdad teaching hospital and x- ray institute who underwent imaging between January 2011 and fifteenth of august 2012.unsuspected Extraspinal findings (incidental findings) by MRI spine and with correlation to the sex, age group, types of these findings and the benefit of their early detection. Results: From the 507 patients, incidental finding were detected in 83 patients (16.37 %) some of them have more than one incidental finding, this result showed significant association with age above 60 years, (p≤0.05) Conclusion: A systematic approach to the MRI of the spine should include assessment of tissues and organs outside the region of clinical interest to detect and report any incidental abnormality which could have significant impact on patient’s management.